Intrinsic flavor violation for massive neutrinos - Nishi, C. C. [UNESP] (My University, 2008)
It is shown that intrinsic neutrino flavor violation invariably occurs when neutrinos are created within the standard model augmented by the known massive neutrinos, with mixing and nondegenerate masses. The effects are very small but much greater than the naive estimate Δm2/Eν2 or the branching ratio of indirect flavor violating processes such as μ→eγ within the SM. We specifically calculate the probability (branching ratio) of pion decay processes with flavor violation, such as π→μν̄e, showing nonzero results. © 2008 The American Physical Society.